The role of constitutional reforms after the Arab spring in consolidating human rights and democracy in the MENA - Kedjali, Zakaria (Journal of Human Sciences, 2023)
Legal and constitutional reforms are becoming a reoccurring event in our region, at times it tries to implement the latest adopted doctrines as introduced by judges, scholars or international law, at other times it is the popular pressure which leads the governments to adopt change, much like what happened after what is known as the arab spring, or like the Hirak in algeria which represents such a pressure and which led to the adoption of a new constitution. This paper argues that despite how important these formal reforms maybe (especially in executing pressure by the civil society) they are not enough unless they are coupled with two conditions, first a genuine political will, and second, societal roots for the rules and changes that being imported, the latter would be reflected in the social norms upon which one could implement legal rules. The paper will focus on the Algerian case in the last two part.